Analisis Kebutuhan Tenaga Admisi IGD dengan Metode Analisis Beban Kerja Kesehatan di Rumah Sakit Khusus Daerah Duren Sawit - Sadono Hadi Saputro; Muhammad Rezal; Muhammad Fuad Iqbal; Laela Indawati (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Admission services in the emergency department (IGD) are an important part of hospital operations that require effective management to support health services. Optimal medical record management requires human resource planning according to actual workload. This research was conducted to analyze the need for admission registration at the Duren Sawit Regional Special Hospital (RSKD) with a quantitative approach using descriptive methods. The research results show that RSKD Duren Sawit has Standard Operational Procedures (SPO) which refer to Minister of Health Regulation No. 33 of 2015 in planning health human resource needs (HRK). Health workload analysis indicates that the ideal requirement is seven admissions officers, while currently only five officers are available, so there is a shortage of two officers. Factors that influence the workload of admission registration include: Man, namely the limited number of officers in the medical records unit, Machine, namely the BPJS server down and power outages, Material, namely the mixed admissions work room with the cashier so the medical record files are still in one room, Method, namely the HR application process at RSKD Duren Sawit found no obstacles, Money, namely there is no budget planning for additional officers in the medical records unit.